The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1073/pnas.87.7.2588
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and genetic characterization of a radiation-induced structural rearrangement in mouse chromosome 2 causing mutations at the limb deformity and agouti loci.

Abstract: Molecular characterization of mutations in the mouse, particularly those involving agent-induced major structural alterations, is proving to be useful for correlating the structure and expression of individual genes with their function in the whole organism. Here we present the characterization of a radiation-induced mutation that simultaneously generated distinct alleles of both the limb deformity (ld) and agouti (a) loci, two developmentally important regions of chromosome 2 normally separated by 20 centimor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 16 publications
3
31
0
Order By: Relevance
“…Analysis of eyes from homozygous IdLn2 mice (Woychik et al, 1990a) revealed a variable degree of lens fibre degeneration that was never observed in wild-type littermates, However, no such eye lesions were present in homozygous mice of the IdJ allele, which probably corresponds to the strongest existing Id allele (for details see Maas et al, 1994). Therefore, it is unclear at present if the observed eye phenotype Id1& mice is caused by mutation of the Id gene.…”
Section: Is There a Role For The Id Gene Products During Eye And Lensmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of eyes from homozygous IdLn2 mice (Woychik et al, 1990a) revealed a variable degree of lens fibre degeneration that was never observed in wild-type littermates, However, no such eye lesions were present in homozygous mice of the IdJ allele, which probably corresponds to the strongest existing Id allele (for details see Maas et al, 1994). Therefore, it is unclear at present if the observed eye phenotype Id1& mice is caused by mutation of the Id gene.…”
Section: Is There a Role For The Id Gene Products During Eye And Lensmentioning
confidence: 99%
“…Five independent alleles of the Id mutation have been identified to date and all cause a pleiotropic mutant phenotype affecting morphogenesis of limbs and kidneys (Cupp, 1960;Green, 1962;Kleinebrecht et al, 1982;Woychik et al, 1985Woychik et al, , 1990a and results in shortening of the antero-posterior limb axis (Zeller et al, 1989). Limb pattern formation is severely affected and results in deletions and fusions of limb skeletal elements along the antero-posterior axis.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the adult ldJ population underrepresents the fraction of ldJlldJ mice with the neonatal lethal bilateral renal agenesis phenotype, and would bias it in favor of detection of any ldJlldJ mice with two kidneys. Thus, the ldJlldJ mice are much more severely affected than either ldoRIldoR or ldTgHdl ldTgHd mice, as judged by comparison of either the ldoR or ldTgHd homozygous populations to either of the ldJl EdJ populations studied (for the 1811dJ mice tabulated in (Woychik et al, 1990a;Messing et al, 1990;Vogt et al, 1992). Interestingly, the phenotype observed in the ldId allele appears also to involve a defect at the level of the ureter or renal hilum, because of the 80 homozygous fetuses examined, in addition to 7 fetuses with the renal agenesis phenotype, 10 other fetuses manifested hydronephrosis or megaureter, and 6 or 9 post-weaning homozygotes had various degrees of hydronephrosis and hydroureter (Woychik et al, 1990a).…”
Section: Renal Agenesis In Ldlld Mice Occurs Stochasticallymentioning
confidence: 99%
“…Thus, the ldJlldJ mice are much more severely affected than either ldoRIldoR or ldTgHdl ldTgHd mice, as judged by comparison of either the ldoR or ldTgHd homozygous populations to either of the ldJl EdJ populations studied (for the 1811dJ mice tabulated in (Woychik et al, 1990a;Messing et al, 1990;Vogt et al, 1992). Interestingly, the phenotype observed in the ldId allele appears also to involve a defect at the level of the ureter or renal hilum, because of the 80 homozygous fetuses examined, in addition to 7 fetuses with the renal agenesis phenotype, 10 other fetuses manifested hydronephrosis or megaureter, and 6 or 9 post-weaning homozygotes had various degrees of hydronephrosis and hydroureter (Woychik et al, 1990a). Although the hydronephrosisl hydroureter phenotype has been observed only in the ldrd allele and thus may represent a strain difference or incidental cosegregating mutation, the finding of a hydronephrosis and hydroureter phenotype in ldrdl ld'& mice is consistent with a primary effect of the limb deformity mutation at the level of ureteral development.…”
Section: Renal Agenesis In Ldlld Mice Occurs Stochasticallymentioning
confidence: 99%
See 1 more Smart Citation